Temporal organization among pollination systems in a tropical seasonal forest - Genini, Julieta [UNESP]; Guimarães, Paulo R.; Sazima, Marlies; Sazima, Ivan; Morellato, Leonor Patrícia Cerdeira [UNESP] (Springer Nature, 2021)
Temporal constancy of pollination systems is essential for the maintenance of pollinators through time. Community-level assessment of flowering phenology allows understanding variations across seasons and years and the risks of decoupling flowering and pollinators’ activity. We evaluated flowering patterns and temporal diversity of pollination systems in a tropical seasonal forest. We asked whether the temporal organization of flowering times differs among pollination systems; if there is a constancy of pollination systems through the year, since climate and phylogenies constraint flowering time; if there is a prevalent flowering pattern by pollination system, and if the temporal organization of pollination systems by modularity analyses is coherent with grouping by pre-defined seasons. We characterized 10 pollination systems, examined flowering strategies, climate cues and phylogenetic constraints. Pollination by large-to-medium bees dominated (49.2%), followed by diverse insects (22.1%) and flies (14.7%). The remaining systems represented 14% of species. Flowering occurred year-round for most pollination systems, predominating the seasonal flowering strategy. Flowering patterns ranged from aggregated to nested, and random. Climate affected the flowering of most pollination systems, but there was no phylogeny constraint. Modularity grouped pollination systems differently than rainfall seasonality. Contrasting the expectations of reduced temporal constancy, most systems were present year-round, facilitating the exploitation of floral resources by pollinators. Diversity of pollination systems remained constant despite climate seasonality, indicating that several factors influence the optimum flowering time for pollination in seasonally dry vegetations. Global warming may disrupt phenological patterns and the temporal organization of plant communities, a matter for future studies.
Keywords: Climate; Flowering patterns; Flowering strategy; Pollination systems; Temporal organization